Evaluating Arabic language book for third intermediate class according to social and Linguistic standards in Iraq from the teachers ‘view - Hussein Ibrahim, Azhar (Journal of College of Education, 2021)
The study aims to evaluate the Arabic language book for the third intermediate class based on social and Linguistic standards and the researcher followed the classroom curriculam and the study community consists of thirt intermediate teachers(males and females) of aboud (1359) teachers and the number of selected sample of teacher that choosen randomly is(272) (128male) and (144female)and the researcher decigned asurvey consisted of two fields,The first field the Linguistic stundards and it‘s number(19standard) and the second field the social standard of (27) standard then presented the tool to alury members to ensure it‘ s validity. The constancy was measurl by distributing it on pilot study and the constancy rate was (0,85) Cronbach‘S Alpha the study showed that the degree of evaluating of Arabic Languaeg book third intermediate class was medu according to the teachers ‘view(Males and females) in the governmeut schools in Baghdad city was medium. The researcher used the following statistical means: the werghted mean and the percentage weight to reach to the following results: Arabic language book third intermediate class focwed on some of the social values and it‘s treatment but it neglect some of the social and Linguistic standards According to the results of the study the researcher recommended take the opinions of Arabic teachers (Males and females) in their consideration to improve this book and Let hem particicipate in editing and developing commities and may seek review of edihny the Arabic language book to cope with the social and linguistic standards the researcher presented suggestions for the future studies ,some of the hom are: making astndy for the primary stage to assess the Arabic language book according to the social and Linguistic standards